2017
DOI: 10.1080/10826084.2017.1305416
|View full text |Cite
|
Sign up to set email alerts
|

Experienced-Based Versus Scenario-Based Assessments of Shame and Guilt and Their Relationship to Alcohol Consumption and Problems

Abstract: Shame appears to be more central to the experience of problematic drinking than guilt. Results also support the idea that guilt/shame proneness is distinct from experienced shame and guilt. Incorporating this distinction appears to account for the inconsistencies in the literature regarding how shame and guilt are related to drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Several studies have demonstrated that shame is associated with addictive behaviors (Luoma et al, 2017;Treeby & Bruno, 2012) and with increased problematic alcohol use (Treeby & Bruno, 2012). Additional research has found that individuals with depressive symptoms experience increased shame following an adverse event, which then leads to self-criticism and rumination (Kim et al, 2011;McGaffin et al, 2013).…”
Section: Outcomes Of Shamementioning
confidence: 99%
“…Several studies have demonstrated that shame is associated with addictive behaviors (Luoma et al, 2017;Treeby & Bruno, 2012) and with increased problematic alcohol use (Treeby & Bruno, 2012). Additional research has found that individuals with depressive symptoms experience increased shame following an adverse event, which then leads to self-criticism and rumination (Kim et al, 2011;McGaffin et al, 2013).…”
Section: Outcomes Of Shamementioning
confidence: 99%
“…Concealment is associated with poor psychological health outcomes among people with many types of CSIs, including minority sexual orientations (Frost et al, 2007;S. D. Jackson & Mohr, 2016;Riggle et al, 2017;Schrimshaw et al, 2013), multiple sclerosis (Cook et al, 2017), and histories of intimate partner violence (Sylaska & Edwards, 2014) and substance abuse (Luoma, Guinther, Potter, & Cheslock, 2017). Larson, Chastain, Hoyt, and Ayzenberg (2015) conducted a meta-analysis of 137 studies that used the Self-Concealment scale to measure concealment with various populations (e.g.…”
Section: Concealmentmentioning
confidence: 99%
“…Feelings of shame relate to the individual's own perception that they are flawed or that others have that same belief while guilt signals to the self that we have done something wrong or hurtful (Luoma, Guinther, Potter, & Cheslock, 2017). The self-medication hypothesis also theorizes that substance use is a way of dealing with problems of self-esteem and self-care.…”
Section: Sud On Shame and Guiltmentioning
confidence: 99%
“…Feelings of guilt are common both in patients with SUD and patients with ADHD (Able et al, 2007;Luoma et al, 2017), and it may well be that recognition between patients regarding this feeling is abundant. The psychoeducational segments of the treatment facilitated understanding of guilt and normalized its presence in light of repeated failures in everyday life due to ADHD symptomatology and alcohol and drug use.…”
Section: Sud and Adhd On Guiltmentioning
confidence: 99%
See 1 more Smart Citation